Q=C(2+aF)

Rewrite the equation as C(2+aF)=Q.

C(2+aF)=Q

Divide each term in C(2+aF)=Q by C.

C(2+aF)C=QC

Cancel the common factor of C.

Cancel the common factor.

C(2+aF)C=QC

Divide 2+aF by 1.

2+aF=QC

2+aF=QC

2+aF=QC

Subtract 2 from both sides of the equation.

aF=QC-2

Divide each term in aF=QC-2 by a.

aFa=QC⋅1a+-2a

Cancel the common factor of a.

Cancel the common factor.

aFa=QC⋅1a+-2a

Divide F by 1.

F=QC⋅1a+-2a

F=QC⋅1a+-2a

Simplify each term.

Multiply QC and 1a.

F=QCa+-2a

Move the negative in front of the fraction.

F=QCa-2a

F=QCa-2a

F=QCa-2a

Solve for F Q=C(2+aF)